Family values divorce, working women, and reproductive rights in Twentieth-Century America - Heinemann, Isabel 1971- (De Gruyter Oldenbourg, 2023)
Clashes over the American family and its values have always implicitly or explicitly addressed issues of gender and highlighted the significance of present and future families to American society. This is the insight underpinning Isabel Heinemann's groundbreaking study, which traces, over the course of the twentieth century, debates on the family and its role; the relationship between the individual and society; and individual decision-making rights as well as their denial or curtailment. Unpacking these issues in a vivid and innovative analysis, the book recounts the prehistory of current conflicts over the family and gender while illuminating the relationship between social change, normative shifts, and the counter-movements spawned in response to them